2022
DOI: 10.2147/ijgm.s356540
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Analysis of the Risk Factors and Drug Resistance of Pathogenic Bacteria in Systemic Inflammatory Response Syndrome After Ureteroscopic Holmium Laser Lithotripsy for Impacted Ureteral Calculi

Abstract: Objective To investigate the risk factors, pathogen distribution, and drug resistance of systemic inflammatory response syndrome (SIRS) after holmium laser ureteroscopic lithotripsy for impacted ureteral calculi (HLULIUC). Patients and Methods The clinical data of 293 patients with HLULIUC in our hospital from October 2017 to February 2021 were retrospectively collected, including age, BMI, stone size, operation time, urine routine, urine culture, basic illness, complet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Postoperative nosocomial infections occurred in 27.6% of the patients in this study, which is higher when compared to the previous literature. Yuan et al 15 retrospectively collected data of 293 patients who underwent laser ureteroscopic lithotripsy, and found that 17.75% of patients developed postoperative infections, while Mi et al 16 reported that the incidence of infection after flexible ureteroscopy combined with holmium laser lithotripsy was 9.7%. The observed higher incidence in our results may be related to the smaller sample size and selection bias in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative nosocomial infections occurred in 27.6% of the patients in this study, which is higher when compared to the previous literature. Yuan et al 15 retrospectively collected data of 293 patients who underwent laser ureteroscopic lithotripsy, and found that 17.75% of patients developed postoperative infections, while Mi et al 16 reported that the incidence of infection after flexible ureteroscopy combined with holmium laser lithotripsy was 9.7%. The observed higher incidence in our results may be related to the smaller sample size and selection bias in this study.…”
Section: Discussionmentioning
confidence: 99%